Photoresponsive Cellulose Nanocrystals - Dimitris S Argyropoulos; Hasan Sadeghifar; Ilari Filpponen (Nanomaterials and Nanotechnology)
In this communication a method for the creation of fluorescent cellulose nanoparticles using click chemistry and subsequent photodimerization of the installed side‐ chains is demonstrated. In the first step, the primary hydroxyl groups on the surface of the CNCs were converted to carboxylic acids by using TEMPO‐mediated hypohalite oxidation. The alkyne groups, essential for the click reaction, were introduced into the surface of TEMPO‐ oxidized CNCs via carbodiimide‐mediated formation of an amide linkage between monomers carrying an amine functionality and carboxylic acid groups on the surface of the TEMPO‐oxidized CNCs. Finally, the reaction of surface‐modified TEMPO‐oxidized cellulose nanocrystals and azido‐bearing coumarin and anthracene monomers were carried out by means of a click chemistry, i.e., Copper(I)‐catalyzed Azide‐Alkyne Cycloaddition (CuAAC) to produce highly photo‐responsive and fluorescent cellulose nanoparticles. Most significantly, the installed coumarin and/or anthracene side‐chains were shown to undergo UV‐induced [2+2] and [4+4] cycloaddition reactions, bringing and locking the cellulose nanocrystals together. This effort paves the way towards creating, cellulosic photo responsive nano‐arrays with the potential of photo reversibility since these reactions are known to be reversible at varying wavelengths.